Intervenções urbanas compensatórias do Vila Parque e a sustentabilidade dos territórios periféricos de Santana de Parnaíba-SP/Brasil - Oliveira, Murillo Calixto Navarro (2021)
Santana de Parnaíba is the municipality in the western sub-region of the Metropolitan Region of São Paulo that obtained the highest population growth in recent decades, characterized by an accelerated urbanization process that resulted in a situation marked by the housing deficit and occupation of risk areas by the low-income population. This description is the same as observed in most Brazilian cities, arising from the difficulties that the government has in solving urban problems, in view of the lack of resources, absence of medium and long-term planning and property speculation. Thus, the objective of this dissertation was to analyze the contributions of compensatory urban interventions, inherent to the construction of the "Vila Parque" condominium, to increase the sustainability of the peripheral territories of Santana de Parnaíba-SP/Brazil. This study was based on the exploratory research methodology, which was approached in a qualitative way, from a systematic review of structured literature, data collection and content analysis, with the application of questionnaires to residents and interviews with municipal public officials. In the literature review carried out, no specific references or methodology were found for the assessment of sustainability in peripheral areas, thus increasing the relevance of new studies that consider the particularities of these poor regions. In this way, through a practical demonstration, the results contribute to the assessment of the different aspects of the dimensions of urban sustainability, aimed at poor and vulnerable territories. In addition, it was observed that the action of private capital on urban space, when properly directed by the local government, based on the use of existing urbanistic instruments, can guarantee socio-territorial development and inclusion, in favor of the rights to the city and urban life.